Strategi Pemasaran Produk Palastik (Paving Blok Limbah Plastik) melalui Pelatihan bagi TPST Himalaya Desa Palopo Kecamatan Marisa Kabupaten Pohuwato - Fatmawati, Fatmawati; Pertiwi, Erse Drawana; Rudi, Rudi; Nasrul, Muhammad; Ismail, Yulan (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Plastic waste found in Pohhuwato Regency, especially Marisa District, is processed into brick products. The Beginner Community Empowerment Team (PMP) in collaboration with the Himalaya TPST (Integrated Waste Processing Site) then processes the plastic waste into paving blocks. The resulting product is named Palastik (Plastic Waste Paving Block). The purpose of this activity is to provide knowledge to Himalaya TPST partners regarding the marketing strategy for Palastik products. This activity uses the Community service activity method carried out using an approach consisting of lectures, discussions, and offline and online promotional practices. The results of the activity showed an increase in participants' understanding of the marketing mix and the use of social media as a promotional strategy. This activity is expected to encourage sustainable marketing of products based on recycled plastic waste.ABSTRAKSampah plastik yang terdapat di Kabupaten Pohhuwato, khususnya Kecamatan Marisa diolah menjadi produk batako. Tim Pemberdayaan Masyarakat Pemula (PMP) bekerja sama dengan TPST (Tempat Pengolahan Sampah Terpadu) Himalaya kemudian mengolah limbah plastik tersebut menjadi paving blok. Produk yang dihasilkan diberi nama Palastik (Paving Blok Limbah Plastik). Tujuan kegiatan ini yaitu untuk memberikan pengetahuan kepada mitra TPST Himalaya mengenai strategi pemasaran produk Palastik. Kegiatan ini menggunakan metode Kegiatan pengabdian masyarakat dilakukan dengan menggunakan pendekatan yang terdiri dari ceramah, diskusi, dan praktik promosi offline dan online. Hasil kegiatan menunjukkan peningkatan pemahaman peserta tentang bauran pemasaran serta penggunaan media sosial sebagai strategi promosi. Kegiatan ini diharapkan dapat mendorong pemasaran berkelanjutan produk berbasis daur ulang limbah plastik.